2006
DOI: 10.1017/s0950268806005954
|View full text |Cite
|
Sign up to set email alerts
|

Sustained high levels of stored drinking water treatment and retention of hand-washing knowledge in rural Kenyan households following a clinic-based intervention

Abstract: Nyanza Province, Kenya is characterized by poor water quality and high diarrhoea prevalence. To address these problems, nurses in a maternal and child health clinic in Homa Bay, Kenya were trained in household water chlorination with a locally available, social marketed product, and in six steps of proper hand washing. They were asked to communicate this information to their clients. Interviews immediately following the training by nurses were conducted on 220 clients, of whom 168 (76%) reported being taught b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 17 publications
10
74
1
Order By: Relevance
“…However, other studies in Uganda have demonstrated less frequent use of cotrimoxazole prophylaxis in a similar HIV-infected population (Watera, 2006) and low utilization (6%) of insecticide treated bednets in children (Davis, 2006). Also, studies in other African settings have demonstrated substantially lower use of disinfectant solution attributable to social marketing in Safe Water System programmes (Thevos, 2000;Parker, 2006). Fourth, because of limited resources, we were unable to measure the health impact of the different interventions.…”
Section: Discussionmentioning
confidence: 98%
“…However, other studies in Uganda have demonstrated less frequent use of cotrimoxazole prophylaxis in a similar HIV-infected population (Watera, 2006) and low utilization (6%) of insecticide treated bednets in children (Davis, 2006). Also, studies in other African settings have demonstrated substantially lower use of disinfectant solution attributable to social marketing in Safe Water System programmes (Thevos, 2000;Parker, 2006). Fourth, because of limited resources, we were unable to measure the health impact of the different interventions.…”
Section: Discussionmentioning
confidence: 98%
“…Previous health facility-based WASH intervention studies have mostly focused on integrating WASH into clinic-based antenatal services. [28][29][30][31][32][33][34][35] In Kenya, a child and maternal health clinic-based intervention that promoted chlorination of household drinking water as part of regular nursing practice resulted in 71% of households having detectable chlorine in stored drinking water 1 year later. 29 Consistent with this, in Malawi, a health facilitybased water treatment and hygiene intervention integrated into a antenatal program, resulted in 71% of households having detectable chlorine in stored drinking water at the 10-month follow-up, compared with only 9% of households at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are very few published studies that have evaluated the impact of health facility-based WASH interventions for households, and none, to our knowledge, that have evaluated the impact this form of intervention focused on household members of diarrhea patients. [28][29][30][31][32][33][34][35] In an effort to develop a low-cost standard of care for the household members of cholera patients, we recently developed a hospital-based handwashing with soap and water treatment intervention entitled Cholera-Hospital-Based Intervention for 7 days (CHoBI7). In our recent randomized controlled trial (RCT) of this intervention where CHoBI7 was compared with the standard message given in Bangladesh to diarrhea patients at discharge on ORS use, we observed a 47% reduction in the incidence of overall cholera infections (symptomatic and asymptomatic), and a significant reduction in symptomatic cholera infections among household members of cholera cases in the intervention compared with the control arm during the 1 week intervention period.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of availability of the product did not appear to be a major barrier. In previous studies, the principal barriers to product use were cost, knowing where to buy the product, and taste and smell [30][31][32]. Improved education about the product and the importance of water treatment could help lower some of these barriers.…”
Section: Discussionmentioning
confidence: 99%